СИНТЕЗ НАНОРОЗМІРНИХ Li-ПРОВІДНИХ ЧАСТОК ЗІ СТРУКТУРОЮ NASICON - Lisovskyi, Ivan; Solopan, Serhii; Khomenko, Volodymyr; Barsukov, Viacheslav; Belous, Anatolii; V’yunov, Oleg (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2019)
The development of autonomous battery packs is one of the important energy problems. Nowadays, typical batteries are based on a liquid electrolyte. However, they have number of disadvantages, including restrictions on their design and size, limitations in the operating temperature range, and also dangerous because of the threat of leakage of the electrolyte. It is possible to achieve miniaturization of current sources using a solid electrolyte. In addition, the use of batteries will become more safety by eliminating the threat of leakage of the electrolyte using a solid electrolyte. However, solid state batteries have a number of other disadvantages. The most serious of them are: the stability of the solid electrolyte in contact with the lithium anode and the high resistance of the cathode/solid electrolyte interface. In recent decades, systems like Li1.3Al0.3Ti1.7- (PO4)3 (LATP) with NASICON-type structure have been actively investigated. This material is resistant to water, air and fire, have high ionic conductivity (10–4–10–3 S/cm), have a wide window of electrochemical stability and is stable in contact with metallic lithium. The key to solving the problem of high resistance of the cathode/solid electrolyte interface is modification of the cathode material by introducing solid electrolyte particles to create core/shell structures and forming ion-conducting channels. Therefore, it is necessary to develop methods for the synthesis of LATP, which: a) will allow to obtain large quantities of material for the manufacture of solid electrolytes; b) will enable the production of nanoscale particles for the modification of the cathode material. In this work, the influence of the synthesis method (solid phase method, sol-gel method, microemulsion production method) on the properties of the resulting particles was studied. The structure of the nanoparticles, their phase and microstructural features were investigated. Preliminary testing of received materials in electrochemical systems was held.